2013
DOI: 10.1183/09031936.00147612
|View full text |Cite
|
Sign up to set email alerts
|

APOMand high-density lipoprotein cholesterol are associated with lung function and per cent emphysema

Abstract: Chronic obstructive pulmonary disease (COPD) is linked to cardiovascular disease; however, there are few studies on the associations of cardiovascular genes with COPD. We assessed the association of lung function with 2,100 genes selected for cardiovascular diseases among 20,077 European-Americans and 6,900 African-Americans. We performed replication of significant loci in the other racial group and an independent consortium of Europeans, tested the associations of significant loci with percent emphysema, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 99 publications
(91 reference statements)
4
41
0
2
Order By: Relevance
“…In turn, HDL might increase inflammation by its protein cargo, including serum amyloid A1, a major apolipoprotein in HDL during inflammation . Interestingly, recent large epidemiological study has demonstrated that higher HDL is associated with lower FEV 1 /FVC ratio and greater percent of emphysema in COPD . Our report lines this observation, indicating HDL as a potent determinant of RBM thickening and higher LAA%.…”
Section: Discussionsupporting
confidence: 85%
“…In turn, HDL might increase inflammation by its protein cargo, including serum amyloid A1, a major apolipoprotein in HDL during inflammation . Interestingly, recent large epidemiological study has demonstrated that higher HDL is associated with lower FEV 1 /FVC ratio and greater percent of emphysema in COPD . Our report lines this observation, indicating HDL as a potent determinant of RBM thickening and higher LAA%.…”
Section: Discussionsupporting
confidence: 85%
“…Lipoproteins may have pathophysiologic importance in lung disease 82 ; differences in apolipoprotein B have been described in association with lung function and COPD 83,84 , and a recent study identified an association between SNPs near APOM , lung function, and emphysema 85 . Similarly, our GRAIL analysis suggested a role for oncostatin M and its receptor, which may be of interest in COPD and emphysema 86,87 .…”
Section: Discussionmentioning
confidence: 99%
“…Another top association was with rs679620 in MMP3, which is in the same region recently associated with severe COPD in a GWAS meta-analysis (6). The variant rs2070600 in AGER is associated with COPD and quantitative computed tomography-identified emphysema, and was first identified as genome-wide significant in GWASs of FEV 1 /FVC ratio (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%